2017
DOI: 10.1136/bmjopen-2017-016907
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the McGrath MAC and Macintosh laryngoscope for tracheal intubation in 2000 patients undergoing general anaesthesia: the randomised multicentre EMMA trial study protocol

Abstract: IntroductionThe direct laryngoscopy technique using a Macintosh blade is the first choice globally for most anaesthetists. In case of an unanticipated difficult airway, the complication rate increases with the number of intubation attempts. Recently, McGrath MAC (McGrath) video laryngoscopy has become a widely accepted method for securing an airway by tracheal intubation because it allows the visualisation of the glottis without a direct line of sight. Several studies and case reports have highlighted the bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Previous studies with the Bonfils have demonstrated a steeper learning curve compared to DL using the Macintosh blade [ 15 ]. Since VL plays an important role in the management of the difficult airway or failed airway after DL [ 20 ], it is more prudent to assess the learning curve between VS and VL to assess any differences. Although we expected the VS to have a faster learning curve, both devices demonstrated a similar learning curve, which could be a reflection of the common initial steps taken for both DL and VL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with the Bonfils have demonstrated a steeper learning curve compared to DL using the Macintosh blade [ 15 ]. Since VL plays an important role in the management of the difficult airway or failed airway after DL [ 20 ], it is more prudent to assess the learning curve between VS and VL to assess any differences. Although we expected the VS to have a faster learning curve, both devices demonstrated a similar learning curve, which could be a reflection of the common initial steps taken for both DL and VL.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently used instrument just before cricothyrotomy was a videolaryngoscope. This is an increasingly popular method for intubation offering better and faster visualisation of the laryngeal situs for the provider and the assisting staff than direct laryngoscopy does 27–31. All applied instruments are part of most DAM algorithms 2–4 23–25.…”
Section: Discussionmentioning
confidence: 99%
“…An intubation attempt was defined as an introduction of the laryngoscope blade into mouth and its removal regardless of whether an ETT was successfully inserted. [7] More than 3 attempts were considered as failure of intubation. Secondary outcomes included manoeuvres used to facilitate intubation and Time to Intubation (TTI).…”
Section: Methodsmentioning
confidence: 99%